Success Factors of Small and Medium-Sized International Enterprises in the Chinese Market from the Perspective of Polish Direct Investment (Cultural Approach) - Iwińska-Knop, Krystyna; Linka, Jarosław (Comparative Economic Research. Central and Eastern Europe, 2011)
Globalization has resulted in increasing transfer of firms operations, regardless of their size, to other countries. The recent dynamic emergence of China in the global economy, connecting with the vast inflows of foreign direct investment in their territory and common adjustments problems of many Western companies, has resulted in growing interest for best suitable business practices to this culturally and socially different environment. In this article, the key factors critical to the success of international companies in this region are introduced, with particular consideration to indigenous cultural elements and specific operation requirements of small and medium-sized enterprises in Business-to-Business sectors. The presented information are based on the broad literature review, five years of direct observation and thirty eight interviews conducted with Polish managers directly residing in China. In addition, some practical recommendations for managers and further research are given.